2020
DOI: 10.4038/jas.v15i3.9031
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Salmonella spp. from Broiler Chicken Meat in Sri Lanka and their Antibiotic Resistance

Abstract: Purpose : Salmonella infections continue to be a global problem with millions of humans and animal cases occurring annually. Broiler chicken plays a significant role causing Salmonella infections in Sri Lanka. Consumption of food contaminated with antimicrobial resistant Salmonella aggravates the problem. This study isolated, identified, and serotype the Salmonella spp. from broiler chicken meat in Sri Lanka and examined their antimicrobial susceptibility to be used in establishment of control measures. Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
2
3
0
2
Order By: Relevance
“…This study showed isolation of Salmonellae in percentage of 11 (11/100). Similar isolation rates were previously reported by Kaoud et al (2018) and Soliman et al (2018) who isolated Salmonellae from the Egyptian broiler flocks in rates of 11.33 % and 10.37%, respectively, Moreover, in Seri Lanka, Jayaweera et al (2020) demonstrated isolation of Salmonellae from chickens in rate of 11.6%. However, Egyptian studies of Sedeik et al (2019) and El-Sheikh et al (2019) showed isolation of Salmonellae from broiler chicks in rates of 7.5% and 16%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed isolation of Salmonellae in percentage of 11 (11/100). Similar isolation rates were previously reported by Kaoud et al (2018) and Soliman et al (2018) who isolated Salmonellae from the Egyptian broiler flocks in rates of 11.33 % and 10.37%, respectively, Moreover, in Seri Lanka, Jayaweera et al (2020) demonstrated isolation of Salmonellae from chickens in rate of 11.6%. However, Egyptian studies of Sedeik et al (2019) and El-Sheikh et al (2019) showed isolation of Salmonellae from broiler chicks in rates of 7.5% and 16%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…spvC, cdtB and sefA were not detected in any isolates.Further, invA, hilA, sivH, tolC and cbtB genes have an important role in host cell invasion and presence of these genes is indicative of invasive properties of eld isolates(Ilyas et al, 2017). Our ndings are in accordance with Awad, et al, (2020) andJayaweera, et al, (2020) who reported the presence of invA, hilA, sivH, tolC and cbtB genes in eld isolates from various sources. Our ndings about invA gene are also in agreement with previous report of (Abdelfatah et al, 2018).…”
supporting
confidence: 91%
“…Salmonella spp., and E. coli were previously reported in food specimen by various investigators from both West, East, North and Southern African countries. 26 - 30 Such observation implies that these members of Enterobacteriaceae infecting potential pathogens thrive within the environment in the region. It also indicates that the food specimen both harbours and serve as carrier/distributor of these potential pathogens.…”
Section: Discussionmentioning
confidence: 99%